"By patience, labour and prayer. The voice of the Unseen God in the language of the Bechuana nation." A reflection of the history of Robert Moffat's Setswana Bible (1857) - J. J. Lubbe (Acta Theologica)
The translation of the Bible into Setswana by Robert Moffat in 1857 was the first in an African language in sub-Sahara Africa and also the first Bible to be printed here — at the mission station at Kuruman, 150 years ago. This Bible translation had an enormous influence, reaching the Batswana people in different countries in Southern Africa and is still held in high esteem by them. The question should be asked why? What made Moffat’s Setswana Bible so popular? The relevant primary sources — collected and studied as the focus of this article — suggest that it might have been the daily life and work of this missionary and his wife for nearly half a century amongst the Batswana. Robert and Mary Moffat convinced “the Bechuana nation” to accept and read the Gospel in their own language, by living “the voice of the Unseen God”.